Direct observations of the dissolution of fluorite surfaces with different orientations - Godinho, J.; Putnis, Christine; Piazolo, S. (2014)
Atomic force microscopy has been used to observe the surface dynamics during dissolution of polished fluorite surfaces with different orientations. These surfaces, with an initially high density of atomic scale defects, showed fast changes during the first seconds in contact with a solution. Different types of structures developed on each surface, depending on its initial orientation and solution composition. These structures dissolved slower than the main surface persisting for at least 67.5 days of continuous dissolution. A new interpretation of traditional kinetic and thermodynamic models of dissolution applied to surfaces with a high density of steps is proposed to explain the observations. The new model includes the following: (a) fast initial dissolution at defect sites, (b) formation of a fluid boundary layer at the mineral-solution interface enriched in the dissolving ions, and (c) precipitation of more stable fluorite structures nucleated at surface defects. This model highlights the importance of considering surface defects and crystal orientation for advancing our understanding of processes happening at the mineral-solution interface and for developing more accurate kinetic dissolution and crystal growth models essential in Earth and material sciences. © 2013 American Chemical Society.